การเปรียบเทียบการขยายตัวของเมืองระหว่างก่อนและหลังการเข้าร่วมโครงการ 12 เมืองต้องห้าม...พลาด โดยใช้ภาพถ่ายแสงไฟช่วงกลางคืนจากดาวเทียม กรณีศึกษาจังหวัดสุพรรณบุรี - ไชยคราม, ธัญญรัตน์ (Thai Journal of Science and Technology, 2019)
This study is a comparative analysis of urbanization and urban expand before and after participating 12 hidden gems cities of Suphanburi province which aimed to (1) classify the land in year 2003, 2007, 2015 and 2018 from satellite imageries data from OLS and VIIRS to categorize nighttime light reflection value by setting the period as 20:00-22:00 and then divide the level of urbanization using the technique of Natural Breaks into 4 levels which are non-urbanized area, fairly urbanized area, medium urbanized area and highly urbanized area. The results found out in the periods of before participating 12 hidden gems cities tourism campaign, the expand of urbanization slightly increased from previous years from urban area as 858.647 to 1,201.81 m2 which was 6.40 %. However, after participating in mentioned tourism campaign, urban area expanded from previous years massively which was 25.50 % increased from 1,245.44 to 2,612,13 m2. Accordingly, urban expand in each district also tended to rise every year as urbanization increase found in Muang Suphanburi district and Doem Bang Nang Buat district the highest, which the value of light reflection found in 54-63. (2) study 2 factors affected urbanization which were population density and changes and increase of tourist attractions. As the results, Muang Suphanburi district and Si Prachan district had population density in the highest rank, especially in Muang Suphanburi district, which was increased continuously in every year. From the field survey and interview, it was found that from tourist attractions in studied area 77 attractions divided in built or developed before participating the campaign 54 attractions and built up after participating the campaign 23 attractions, which found that after participating the numbers of tourist attractions has also risen up tremendously by gathering compactly around national highway 340 which affected Muang Suphanburi district to create more facilities for tourists in large amount such as build-ups, business areas, resorts, hotels, which affected the population nearby to move into the areas greatly and made this area as the highest urbanization over the studied areas.